Identification of Genes that Maintain Behavioral and Structural Plasticity during Sleep Loss - Seugnet, Laurent; Dissel, Stephane; Thimgan, Matthew; Cao, Lijuan; Shaw, Paul J. (Frontiers in Neural Circuits, 2017)
Although patients with primary insomnia experience sleep disruption they are able to maintain normal performance on a variety of cognitive tasks. This observation suggests that insomnia may be a condition where predisposing factors simultaneously increase the risk for insomnia and also mitigate against the deleterious consequences of waking. To gain insight into processes that might regulate sleep and buffer neuronal circuits during sleep loss, we manipulated three genes, fat facet (faf), highwire (hiw) and the GABA receptor Resistance to dieldrin (Rdl), that were differentially modulated in a Drosophila model of insomnia. Our results indicate that increasing faf and decreasing hiw or Rdl within wake-promoting large ventral lateral clock neurons (lLNvs) induces sleep loss. As expected, sleep loss induced by decreasing hiw in the lLNvs results in deficits in short-term memory and increases of synaptic growth. However, sleep loss induced by knocking down Rdl in the lLNvs protects flies from sleep-loss induced deficits in short-term memory and increases in synaptic markers. Surprisingly, decreasing hiw and Rdl within the mushroom bodies protects against the negative effects of sleep deprivation as indicated by the absence of a subsequent homeostatic response, or deficits in short-term memory. Together these results indicate specific genes are able to disrupt sleep and protect against the negative consequences of waking in a circuit dependent manner.